2019
DOI: 10.3390/jcm8111835
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic Receptor (ADRB2) Gene Polymorphisms and Risk of COPD Exacerbations: The Rotterdam Study

Abstract: The role of the β2-adrenergic receptor (ADRB2) gene in patients with chronic obstructive pulmonary disease (COPD) is unclear. We investigated the association between ADRB2 variants and the risk of exacerbations in COPD patients treated with inhaled β2-agonists. Within the Rotterdam Study, a population-based cohort study, we followed 1053 COPD patients until the first COPD exacerbation or end of follow-up and extracted rs1042713 (16Arg > Gly) and rs1042714 (27Gln > Glu) in ADRB2. Exposure to inhaled β2-agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…Also, asthma treatment policy that affects doctors’ underlying tendencies to prescribe OCS varies in different countries, which in turn could influence the proportion of asthma exacerbations 38 . In all studies, both SNPs were in complete linkage disequilibrium (D’~1) with each other; as a result, we determined three haplotypes of the four possible haplotypes (Arg16/Gln27 was not reported), which is in line with previous findings 39,40 . Furthermore, considering ethnicity variability in our study populations, we observed different minor allele frequencies in each SNP that resulted in considerable variations in r 2 , which indicates the correlation coefficient of the allele frequencies.…”
Section: Discussionsupporting
confidence: 85%
“…Also, asthma treatment policy that affects doctors’ underlying tendencies to prescribe OCS varies in different countries, which in turn could influence the proportion of asthma exacerbations 38 . In all studies, both SNPs were in complete linkage disequilibrium (D’~1) with each other; as a result, we determined three haplotypes of the four possible haplotypes (Arg16/Gln27 was not reported), which is in line with previous findings 39,40 . Furthermore, considering ethnicity variability in our study populations, we observed different minor allele frequencies in each SNP that resulted in considerable variations in r 2 , which indicates the correlation coefficient of the allele frequencies.…”
Section: Discussionsupporting
confidence: 85%
“…Hussein et al revealed an association of the Arg16 genotypes with highly pronounced respiratory symptoms and frequent exacerbations in Egyptian patients with COPD, and these findings were consistent with our data. However, a recent study by Karimi et al identified that Arg16/Gln27 haplotype reduces the risk of COPD exacerbation in patients using beta‐2‐agonists. The contradictory relationship between genetic variants of ADRB2 and the predisposition to asthma and COPD could be because each of these diseases includes common and specific endotypes and phenotypes, where the alleles of various genes make different contributions .…”
Section: Discussionmentioning
confidence: 98%
“…January 1, 2011), whichever came first. COPD exacerbations were defined as acute episodes of worsening of respiratory symptoms requiring use of either systemic corticosteroids and/or antibiotics (moderate exacerbations), or requiring hospitalisation (severe exacerbations) [ 22 , 23 ]. The outcome was defined as the first moderate to severe COPD exacerbation during follow-up and the date of outcome was taken as the index date.…”
Section: Methodsmentioning
confidence: 99%